Systematic Literature Review: Pengaruh Likuiditas dan Implementasi Good Corporate Governance terhadap Financial Distress - Syifa Indah Aurora Salsabila; Cindy Julia Putri; Dien Noviany Rahmatika (Pusat Riset dan Inovasi Nasional, 2024)
In fluctuating economic conditions, companies are faced with the challenge of maintaining financial stability and avoiding financial distress. The importance of Good Corporate Governance and liquidity management is becoming increasingly crucial in managing financial risk. This research aims to thoroughly understand the influence of liquidity and the implementation of good corporate governance on financial distress. This research uses the Literature Review (SLR) method, there are several journals published from 2019 to 2024 which will later be analyzed regularly. The Systematic Literature Review method can be applied to evaluate, interpret, analyze and identify any existing research that must match the theme of an interesting phenomenon. The research is classified with appropriate ideas and can be grouped with comparable topics to state further problems related to the Influence of Liquidity and the Implementation of Good Corporate Governance on Financial Distress. A total of 55 articles were analyzed in this research. It is hoped that the research results from this study will increase deeper knowledge about the correlation between Liquidity, Good Corporate Governance and Financial Distress, as well as provide useful understanding for academics, regulators and practitioners in managing company financial risks. And given the best understanding of the components that influence Financial Distress, companies can take more proactive action in maintaining their financial stability and improving their overall operational performance.